Das Foyer im Kunstmuseum Luzern - Kunstmuseum Luzern, Luzern (Luzern : Edizioni Periferia, 2015)
Urs Lüthi's descriptions and commentary on his works and his collection of art objects which make up the permanent exhibition in the Foyer of the Kunstmuseum Luzern of which he was the designer.
kunstcatalogus
Keywords: Lüthi, Urs